2021
DOI: 10.3390/md19010034
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Chemopreventive Potential of Phlorotannins-Rich Extract from Brown Algae by Inhibition of Benzo[a]pyrene-Induced P2X7 Activation and Toxic Effects

Abstract: Phlorotannins are polyphenols occurring exclusively in some species of brown algae, known for numerous biological activities, e.g., antioxidant, antiproliferative, antidiabetic, and antiallergic properties. Their effects on the response of human lung cells to benzo[a]pyrene (B[a]P) has not been characterized. Our objective was to in vitro evaluate the effects of a phlorotannin-rich extract obtained from the brown algae Ascophyllum nodosum and Fucus vesiculosus on B[a]P cytotoxic effects. The A549 cell line was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The three cell lines were selected for their different endocrine properties and because they all express functional P2X7 receptors [13,26,34]. Human epithelial pulmonary A549 cells share similar ultrastructural characteristics and cytochromes expression to in situ type II pneumocytes, the most abundant cells in lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three cell lines were selected for their different endocrine properties and because they all express functional P2X7 receptors [13,26,34]. Human epithelial pulmonary A549 cells share similar ultrastructural characteristics and cytochromes expression to in situ type II pneumocytes, the most abundant cells in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Cell incubation: To study the P2X7 receptor and its relationship between apoptosis, the cells were preincubated with either PBS or P2X7 antagonist Brilliant Blue G (BBG) at 25 µM for 15 min [34]. After removal of PBS and BBG, the cells were incubated for 72 h with bisphenol A (5, 10 and 20 µM), diethylstilbestrol (3.75, 7.5 and 15 µM), 4-tert-amylphenol (1, 10 and 50 µM), 4-heptylphenol (1, 10 and 50 µM), triclosan (0.1, 1 and 10 µM), propylparaben (20, 50 and 100 µM), benzyl butyl phthalate (1, 10 and 50 µM), DEHP (1, 10 and 50 µM) and 3-benzylidene camphor (1, 10 and 50 µM) in MEM with 2.5% FBS according to Olivier et al's protocol that describes the JEG-Tox model [35] or DMEM with 2.5% FBS for the HaCaT and A549.…”
Section: Methodsmentioning
confidence: 99%
“…Dutot et al ( 2021 ) studied the chemopreventive potential of phlorotannins based on a benzopyrene induced cytotoxicity study. It was observed that phlorotannin administration helped in counteracting the cytotoxic affects induced by benzopyrene through several pathways such as by preventing the induction of cytochrome P450 activity by benzopyrene, by inhibiting the activation of P2X7 receptor whose activation is reported to induce anti-apoptotic effects, inhibiting actin rearrangement and the production of reactive oxygen species.…”
Section: Broader Applications Of Phlorotanninsmentioning
confidence: 99%
“…The brown seaweed Fucus vesiculosus attracts the attention of specialists as a rich source of polysaccharides, phlorotannins, carotenoids, and other active compounds, which shows potent activities as antioxidants [ 16 ], antiangiogenic [ 17 ], anti-cancer [ 18 , 19 , 20 ], inhibitors of diabetes controlling enzymes [ 21 , 22 ], antimicrobial [ 23 ], anti-inflammatory [ 22 , 24 ], anti-coagulant [ 22 ], skin brightening [ 25 ], etc.…”
Section: Introductionmentioning
confidence: 99%